SHORT CIRCUIT CURRENT LIMIT CONTROL - Pobihailo, V. A. (Systems and Technologies, 2018)
The scientific and practical relevance of improving the functioning of credit limit short – circuit (short circuit), formulated the goal and objectives of research. As a solution proposed research and the way to manage complex limitation of short circuit currents in electricity supply production systems under the reactor – controlled shunt. The algorithm of the system reactor – controlled shunt. For the first time the schemes cause – effect relationships occurrence of short – circuit currents – Figure Ysikavy according to ISO 9004.